Penggunaan Metode Kooperatif Model Student Teams Achievement Divisions (STAD) Untuk Meningkatkan Hasil Belajar Pada Mata Pelajaran IPS Kelas IX SMPN 2 Kapuas Kuala Semester 2 Tahun Pelajaran 2019/2020 - Utami, Retno (ANTHOR: Education and Learning Journal, 2022)
This study uses a class action research design. This research consists of two cycles. Each cycle consists of planning, action, observation, and reflection. The research data were obtained from test and non-test instruments. The test instrument was in the form of quiz questions at the end of cycle I and cycle I, while the non-test instruments were in the form of observation sheets, interviews and questionnaires. Nontest data analysis using qualitative techniques. The results of the successful process in this classroom action research were student activities which increased from cycle I by 61.05% to 94.73% in cycle I. Student skills in cycle I showed a value of 3 or sufficient category, while in cycle I obtained a value of 5 or very good. Recognition of the existence of diversity among students also experienced an increase from a value of 3 in cycle I to 5 in cycle I. The average student learning outcomes in cycle I was 69.82 to 81.25 in cycle I, while the average learning completeness in cycle I by 57.15% increased in cycle I to 85.71%. Based on the results of the study, it can be concludedthat the use of the cooperative learning method type STAD (Student Teams in Achievement Divisions) basic competencies Potential and Distribution of Indonesian Natural Resourcescan increase the activity and learning outcomes of Class 9.2 students of SMP Negeri 2 Kapuas Kuala.